2005
DOI: 10.1037/0894-4105.19.6.787
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of Neurophysiological Processes Involved in Normal Reading and Reading Disability: A Magnetic Source Imaging Study.

Abstract: This longitudinal study examined the development of the brain mechanism involved in phonological decoding in beginning readers using magnetic source imaging. Kindergarten students were assigned to 2 groups: those who showed mastery of skills that are important predictors of proficient reading (low-risk group) and those who initially did not show mastery but later benefited from systematic reading instruction and developed average-range reading skills at the end of Grade 1 (high-risk responders). Spatiotemporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
59
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 51 publications
15
59
1
2
Order By: Relevance
“…A variety of research has demonstrated that interventions based on individual cognitive and neuropsychological processes, including phonological awareness (e.g., Berninger, 2001;Torgesen et al, 1999), successive processing (Churches, Skuy, & Das, 2002), visual/orthographic processing (e.g., Berninger, 2001;Brunsdon, Hannan, Coltheart, & Nickels, 2002), attention training (e.g., Chenault, Thomson, Abbott, & Berninger, 2006;Solan, Shelley-Tremblay, Ficarra, Silverman, & Larson, 2003), working memory (Klingberg, Fernell, & Olesen, 2005), fluency/ processing speed (Torgesen, Rashotte, & Alexander, 2001), and metacognitive and strategy instruction (Vauras, Kinnunen, & Rauhanummi, 1999) can be used to improve word reading and reading comprehension. These interventions lead not only to behavioral or performance changes but also to changes in brain function as well Demonet, Taylor, & Chaix, 2004;Papanicolaou et al, 2003;Shaywitz & Shaywitz, 2005;Simos et al, 2005). In addition, resources are now available to provide practitioners with multiple intervention strategies for cognitive processing deficits, such as Berninger's (2001) Process Assessment of the Learner (PAL), Hale & Fiorello's (2004) School Neuropsychology, Mather & Jaffe's (2002), WJ III: Reports, Recommendations, and Strategies, and Naglieri and Pickering's (2003) Helping Children Learn.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of research has demonstrated that interventions based on individual cognitive and neuropsychological processes, including phonological awareness (e.g., Berninger, 2001;Torgesen et al, 1999), successive processing (Churches, Skuy, & Das, 2002), visual/orthographic processing (e.g., Berninger, 2001;Brunsdon, Hannan, Coltheart, & Nickels, 2002), attention training (e.g., Chenault, Thomson, Abbott, & Berninger, 2006;Solan, Shelley-Tremblay, Ficarra, Silverman, & Larson, 2003), working memory (Klingberg, Fernell, & Olesen, 2005), fluency/ processing speed (Torgesen, Rashotte, & Alexander, 2001), and metacognitive and strategy instruction (Vauras, Kinnunen, & Rauhanummi, 1999) can be used to improve word reading and reading comprehension. These interventions lead not only to behavioral or performance changes but also to changes in brain function as well Demonet, Taylor, & Chaix, 2004;Papanicolaou et al, 2003;Shaywitz & Shaywitz, 2005;Simos et al, 2005). In addition, resources are now available to provide practitioners with multiple intervention strategies for cognitive processing deficits, such as Berninger's (2001) Process Assessment of the Learner (PAL), Hale & Fiorello's (2004) School Neuropsychology, Mather & Jaffe's (2002), WJ III: Reports, Recommendations, and Strategies, and Naglieri and Pickering's (2003) Helping Children Learn.…”
Section: Discussionmentioning
confidence: 99%
“…6 Magnetic resonance imaging (MRI) and positron emission tomography (PET) studies have indicated that structural and functional brain-related factors were found in dyslexic children, for example, visual and temporal processing, magnocellular visual system, cerebellum and hemispheric asymmetry. 1,6,[15][16][17][18][19][20] Reid indicated that there are deficiencies in processing information and decoding words. Children with dyslexia have difficulties when transferring the information from one hemisphere of the brain to another.…”
Section: Aetiology Of Dyslexiamentioning
confidence: 99%
“…As some studies have found that speech perception and production is affected in children with dyslexia at the preschool age, there is some evidence that screening for dyslexia should be conducted during this period. 11,15,16,18,[30][31][32][33][34][35][36][37][38][39][40][41] The third stage is the Concrete Operational Stage from 6 to 11/12 years. Here, it is difficult to distinguish between learned knowledge and that acquired by personal experience.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…In contrast, NIMP who had persistent deficits in reading performance were marked by aberrant activation patterns throughout the reading network (Odegard et al, 2008; Davis et al, 2011), deficiencies in ERP measures (Molfese et al, 2013) and lower functional connectivity between reading-related brain areas (Farris et al, 2011). Furthermore, two longitudinal studies conducted by Simos et al (2005, 2007a) reported on similar spatial and temporal brain activation patterns in normal developing children and 6–8-year-old (Simos et al, 2005) and 8–10-year-old (Simos et al, 2007a) IMP after intervention, which was not observed in NIMP. However, Simos et al (2005, 2007a) did not report on pre-existing differences between IMP and NIMP.…”
Section: Introductionmentioning
confidence: 88%
“…However, studies examining whether there might be neurophysiological differences prior to receiving intervention between IMP and NIMP are less common. To the best of our knowledge only eight studies differentiated between IMP and NIMP (Simos et al, 2005, 2007a; Odegard et al, 2008; Davis et al, 2011; Farris et al, 2011; Rezaie et al, 2011a,b; Molfese et al, 2013). …”
Section: Introductionmentioning
confidence: 99%